Cultivation of microalgae from low salinity water for production of biodiesel by direct transesterification method / Ahmad Rozaimee Mustaffa - Mustaffa, Ahmad Rozaimee (2019)
Microalgae biodiesel are proven to be greater than fossil fuels in terms of life-cycle energy performance. Green microalgae namely, Tetraspora species represents one of the most favorable resources of biodiesel due to relatively high lipid content. The aims of this project are to determine the properties of low salinity water as a growing medium for the growth of Tetraspora species and compare the normal average growth, exponential and logistic models in indoor close (batch) systems. The present study focused on the cultivation of Tetraspora sp. with the fed-batch in 500 ml flasks with an initial 1.0 ml cells cell pipetted in 500 ml culture in the culture medium consists of low salinity water as a growing medium. Growth under Controlled Condition, the algae strains have been successfully grown in an indoor laboratory of UiTM Dungun for 20 days in the low salinity water medium. The comparative studied was also shown that biomass growth models follow normal, exponential and logistics growth model of Tetraspora sp. Determination of the effect carbon dioxide concentration on nutrient deficient (nitrate and phosphate) that accomplishes wastewater treatment. The outcomes indicated that nitrate content under cultivation of Tetraspora sp. was reduced from 5.84±0.11 mg/L to 0.32 ± 0.05 mg/L in 14 days cultivation period. Meanwhile, the phosphate content was removed 100 % from 0.61 ± 0.01 mg/L for 13 days cultivation period. The effect of 15% CO2 aeration, the nitrate is reduced from 5.27 ± 0.06 to 1.80 ± 0.20 mg/L. Meanwhile, for the phosphate concentration is reduced from 0.57 ± 0.15 to 0.13 ± 0.06 mg/L in 14 days cultivation periods. In this research, the determination in percentage of fatty acid methyl ester (FAME) by Direct- transesterification with homogeniser method with the effect of catalyst, reaction temperature, reaction time and ultrasonic-aided with homogenisation have been investigated. From the experimental results was proven that higher yield for the biodiesel from microalgae; Tetraspora sp. was achieved in direct transesterification without catalyst process due to the naturally existence of selfcatalyst such as iron (Fe) of 1153.34±10.40, potassium (K) of 508.98±32.59, calcium (Ca) of 330.43±4.03 and Caesium (Cs) of 153.07±25.70 ppm respectively. The optimum reaction parameters were determined at 60°C temperature and 5 minutes reaction time using high speed homogeniser at 10 000 rpm is significant that contribute to higher average FAME of 98.61 ±1.01 percent. Therefore, the direct transesterification of lipids in microalgae is an effective approach to reduce reaction time and costs of some operation steps such as catalyst recovery and purification of biodiesel can be eliminated through this method. Moreover, the experimental research results obtained in the present study proved that the biodiesel production of Tetraspora sp. is potentially feasible.